Solution-Phase Parallel Synthesis of Acyclic Nucleoside Libraries of Purine, Pyrimidine, and Triazole Acetamides - Pathak, Ashish K. (American Chemical Society, 2014)
[Image: see text] Molecular diversity plays a pivotal role in modern drug discovery against phenotypic or enzyme-based targets using high throughput screening technology. Under the auspices of the Pilot Scale Library Program of the NIH Roadmap Initiative, we produced and report herein a diverse library of 181 purine, pyrimidine, and 1,2,4-triazole-N-acetamide analogues which were prepared in a parallel high throughput solution-phase reaction format. A set of assorted amines were reacted with several nucleic acid N-acetic acids utilizing HATU as the coupling reagent to produce diverse acyclic nucleoside N-acetamide analogues. These reactions were performed using 24 well reaction blocks and an automatic reagent-dispensing platform under inert atmosphere. The targeted compounds were purified on an automated purification system using solid sample loading prepacked cartridges and prepacked silica gel columns. All compounds were characterized by NMR and HRMS, and were analyzed for purity by HPLC before submission to the Molecular Libraries Small Molecule Repository (MLSMR) at NIH. Initial screening through the Molecular Libraries Probe Production Centers Network (MLPCN) program, indicates that several analogues showed diverse and interesting biological activities.